Minyak Kelapa Murni Topikal sebagai Terapi Alternatif Dermatitis Atopik: Analisis - Agustinus, Oktatika (PT Kalbe Farma Tbk., 2024)
Atopic dermatitis, also known as atopic eczema, is a common chronic, recurrent inflammatory condition of the skin. This condition is most commonly experienced in childhood, especially aged 0 to 12 months. The most frequent symptom is itching. This disease greatly affects the patients’ quality of life, psychology and productivity, requiring long-term treatment. To this day, the management of atopic eczema refers to conventional treatment using generic medicines such as oral anti-allergies (antihistamines) and both topical and oral corticosteroids. This article examines potentials of virgin coconut oil as an alternative treatment for atopic dermatitis, various methods of virgin coconut oil production, as well as the composition of the active compounds of virgin coconut oil and their roles in the management of atopic dermatitis.